Case report: Pemigatinib-induced retinopathy: a serial examination of subretinal fluid secondary to an FGFR inhibitor - Daniel Barmas-Alamdari; Daniel Barmas-Alamdari; George Jiao; George Jiao; Ronni Lieberman; Ronni Lieberman (Frontiers in Ophthalmology, 2024)
BackgroundModern chemotherapeutic agents continue to evolve as modern monoclonal antibody treatments are designed to directly target proteins, enzymes, and focal loci. A particular class of these medications, fibroblast growth factor (FGFR) inhibitors, specifically pemigatinib (Pemazyre®; Incyte), has been approved by the US Food and Drug Administration since April 2020 for the treatment of advanced or metastatic cholangiocarcinoma. As it is a relatively new medication, its side-effect profile is manifesting in active clinical practice. The presence of FGFR receptors in the retinal pigment epithelium makes the retina susceptible to potential adverse effects secondary to pemigatinib use.Case presentationA 69-year-old African-American male with a tumor mutation burden 3 (TMB-3) metastatic adenocarcinoma of the liver from primary cholangiocarcinoma, who was undergoing chemotherapy with pemigatinib, was found to have asymptomatic bilateral subretinal fluid accumulation. Serial monitoring with optical coherence tomography (OCT) demonstrated complete resolution of the subretinal fluid while off-cycle and asymptomatic re-accumulation of subretinal fluid while on-cycle, with no significant changes in visual acuity.ConclusionsSubretinal fluid accumulation secondary to pemigatinib may develop during the active treatment cycles without causing any significant visual symptoms for the patient. Serial monitoring demonstrates fluctuations of subretinal fluid during the patient’s on- and off-cycles. This case strengthens the current guidelines for continuing pemigatinib in asymptomatic patients found to have subretinal fluid. Further studies are warranted to identify patients who may be at higher risk for developing subretinal fluid.